Geotechnical risk of the housing associations Sol Naciente and Dos de Febrero, Ciudad Nueva-Tacna. - Cabrera Olivera, Fredy C. (2019)
Objective: Carry out a geotechnical risk analysis of the Intiorko hill sector where the Sol Naciente y Dos de Febrero Housing Association is located in the Ciudad Nueva district, with the objective of preventing settlements and collapsing homes located in the study area. Methodology: A correlational - quantitative design was used, using the documentary review of the studies carried out in the study area as well as interviews with the inhabitants of the area involved. The relevant field investigations were carried out for its processing, analysis and interpretation in the cabinet, which allowed for the final report of the thesis. Results: Geomorphological-geological factors such as: the slope of the medium slope and the characteristics of the colluvial-deluvial deposit are the variables that have created conditions so that the geotechnical characteristics of the foundation soil are not the most suitable for the placement of housing in that zone. Conclusion: The geological-geotechnical conditions of the foundation soil are not adequate for the placement of houses in that area of the Intiorko hill.